A School Eye Health Rapid Assessment (SEHRA) planning tool: Module to survey the magnitude and nature of local needs - Priya Morjaria; Jessica Massie; Andrew Bastawrous; SEHRA Author Group (BMC, 2022)
Abstract Background Eye conditions in children can have negative consequences on visual functioning and quality of life. There is a lack of data on the magnitude of children with eye conditions who need services for effective planning of school eye health programmes. To address this, the School Eye Health Rapid Assessment (SEHRA) tool is being developed to collect data to support school eye health programme planning. Methods The module, 'the magnitude and nature of local needs in school children' is the first of six modules in the SEHRA tool. The module outlines a school-based cluster survey designed to determine the magnitude of eye health needs in children. This paper outlines the survey sampling strategy, and sample size calculations. Results The requirements for the SEHRA survey indicate that in regions where a larger sample size is required, or where fewer schools are recruited to the survey, confidence in the accuracy of the data will be lower. Conclusions The SEHRA survey module 'the magnitude and nature of local needs in school children' can be applied in any context. In certain circumstances, the confidence in the survey data will be reduced.